Risk Factors for Complications in Expander-Based Breast Reconstruction: Multivariate Analysis in Asian Patients. Issue 11 (November 2017) - Suga, Hirotaka; Shiraishi, Tomohiro; Tsuji, Naoko; Takushima, Akihiko
Abstract : Background: There have been many studies examining risk factors for complications in expander-based breast reconstruction after mastectomy, and some patient factors have been identified as risk factors. However, most of the previous studies were based on Caucasian patients. Methods: Asian patients who had a tissue expander placed for immediate breast reconstruction between January 2006 and December 2015 (363 patients and 371 expanders) were analyzed retrospectively. Univariate and multivariate analyses were performed to elucidate risk factors for complications. Results: The rate of skin necrosis was significantly higher in nipple-sparing mastectomy than in other types of mastectomies (12 patients among 107 patients, P = 0.001). The weight of the resected specimen was significantly higher in the group with complications than in the group without complications (444 g compared with 363 g, P = 0.027). Other factors (age, body mass index, smoking, expander type, preoperative chemotherapy, axillary dissection) had no significant effect on complications. Multivariate analysis with a logistic regression showed that a large breast (over 500 g) was the only significant risk factor for complications, with an odds ratio of 3.20 and a 95% confidence interval of 1.33–7.54 ( P = 0.010). Conclusion: In this series of Asian patients, breast size, rather than body mass index, is the most important predictor for complications in expander-based breast reconstruction.